The emergency and delay management in total talus extrusion: Case report and review of literature after 24 months of follow up - Luigi Piscitelli; Michele Bisaccia; Luigi Meccariello; Gabriele Falzarano; Antonio Medici; Daniele Maiettini; Alberto Rebonato; Giuseppe Rinonapoli; Auro Caraffa (Journal of Acute Disease, 2016)
Total talus extrusion is a rare and severe injury. It is burdened by many complications as avascular necrosis and osteomyelitis even if a proper debridement of extruded talus is performed. Few case reports or case series were published, and because of the rarity of this event, there are no guidelines for treatment. We report the first case on an octogenarian man providing a long-term follow-up performing contrast enhanced magnetic resonances. The authors report the case of an octogenarian man who fell from an olive tree reporting a total talus extrusion associated with the fracture of the medial malleolus. After an accurate debridement and washing of the wound, the talus was anatomically repositioned and the fracture was treated with an external fixator. The wound healed with difficulty after 12 months and the patient developed a chronic osteomyelitis of the talar dome and avascular necrosis of talar head. We followed the patient for 24 months performing contrast enhanced magnetic resonances and evaluating the development of the avascular necrosis. Even if we encountered these complications, the treatment allowed the patient to walk without pain, using a talus type shoe and one crutch. Although the literature suggests that an anatomic replacement of talus allows avoiding main complications, we deem that the patient's age is an important biological feature to consider in the prognostic stratification. Moreover, primary talectomy and tibio-calcaneal fusion should be reserved as a salvage procedure. Talus replacement allows an overall good outcome for the patients, retaining height, and allowing a good quality of life.